Influence of Competitive Priorities Strategy on Organizational Performance of Cement Manufacturing Firms in Kenya - Karuga, Charles; Yatich, Henry; Wairimu, Kibe (European Journal of Business and Strategic Management, 2023)
Purpose: The study sought to assess the influence of competitive priorities strategy on organizational performance of cement manufacturing firms in Kenya. Methodology: The study adopted the positivism research philosophy and the concurrent triangulation research design. The target population consisted of eight cement production companies located in the counties of Kisumu, Nairobi, Mombasa, Machakos, Nakuru, and Kajiado were the subject of the study. The study purposely excluded Savannah Cement Limited from the main study since it had been "temporarily" shut down at the time of data collection due to financial and ownership wrangles. Census sampling method and proportional stratified random sampling were used to select 365 employees which included 37 managers, 322 non-managers and 6 CEOs. Both primary and secondary sources were used to gather data for this study, and both quantitative and qualitative data gathering techniques were employed. The qualitative data was analyzed using content analysis technique (Hsieh & Shannon, 2015), while the quantitative data was analyzed using MS Excel 2016 and IBM's SPSS version 28. Findings: the study results indicated that competitive priorities strategies is an operational strategy that is often utilized by the cement manufacturing firms to improve their organizational performance. This was supported by the high level of agreement in all statement by most of the respondents. The study also concluded that competitive priorities strategies had a positive and significant relationship with organizational performance of cement manufacturing firms in Kenya. The regression results led to the rejection of the null hypothesis, thus adopting the alternative hypothesis; competitive priorities strategy has a significant influence on organizational performance of cement manufacturing firms in Kenya. Unique Contribution to Theory, Practice and Policy: The theory used in this study advocated for the need of cement manufacturing firms in Kenya, to focus on identifying strategic resources that are critical for success and improved performance of the industry. Hence, the theory will also be applicable to other studies with such related research topics. The study recommended that the management of cement manufacturing firms in Kenya should invest more in automated systems especially in production and delivery so as to increase their production, operational and supply-chain efficiency. They should also invest in better training programs so as to equip their employees with the necessary skills needed to improve their work efficiency. Moreover, policymakers should also formulate better policies to enhance the competitiveness between manufacturing firms in Kenya.